High-Throughput Flow Cytometry Identifies Small-Molecule Inhibitors for Drug Repurposing in T-ALL. (August 2018) - Perez, Dominique R.; Nickl, Christian K.; Waller, Anna; Delgado-Martin, Cristina; Woods, Travis; Sharma, Nitesh D.; Hermiston, Michelle L.; Loh, Mignon L.; Hunger, Stephen P.; Winter, Stuart S.; Chigaev, Alexandre; Edwards, Bruce; et al.
Kinase inhibitors have dramatically increased patient survival in a multitude of cancers, including hematological malignancies. However, kinase inhibitors have not yet been integrated into current clinical trials for patients with T-cell-lineage acute lymphoblastic leukemia (T-ALL). In this study, we used a high-throughput flow cytometry (HTFC) approach to test a collection of small-molecule inhibitors, including 26 FDA-approved tyrosine kinase inhibitors in a panel of T-ALL cell lines and patient-derived xenografts. Because hypoxia is known to cause resistance to chemotherapy, we developed a synthetic niche that mimics the low oxygen levels found in leukemic bone marrow to evaluate the effects of hypoxia on the tested inhibitors. Drug sensitivity screening was performed using the Agilent BioCel automated liquid handling system integrated with the HyperCyt HT flow cytometry platform, and the uptake of propidium iodide was used as an indication of cell viability. The HTFC dose–response testing identified several compounds that were efficacious in both normal and hypoxic conditions. This study shows that some clinically approved kinase inhibitors target T-ALL in the hypoxic niche of the bone marrow.